Ongoing lithospheric removal in the western Mediterranean: Evidence from Ps receiver functions and thermobarometry of Neogene basalts (PICASSO project). (22nd April 2014) - Thurner, Sally; Palomeras, Imma; Levander, Alan; Carbonell, Ramon; Lee, Cin‐Ty
Abstract The western Mediterranean tectonic system consists of the Betic Mountains in southern Spain and the Rif Mountains in northern Morocco curved around the back‐arc extensional Alboran basin. Multiple tectonic models have been developed to explain the coeval compressional and extensional tectonic processes that have affected the western Mediterranean since the Oligocene. In order to provide constraints on these evolutionary models, we use Ps teleseismic receiver functions (RF), thermobarometric analyses of post‐Oligocene basalts, and previous teleseismic tomography images to investigate the lithospheric structure of the region. Ps RFs were calculated using seismic data from 239 broadband seismic stations in southern Iberia and northern Morocco and thermobarometric analysis was performed on 19 volcanic samples distributed throughout the region. The RF images reveal a highly variable Moho depth (∼25 to ∼55 km), as well as a strong positive, sub‐Moho horizon between ∼45 and ∼80 km depth beneath the central Betic and Rif Mountains, which we interpret to be the top of the previously imaged Alboran Sea slab. Thermobarometric constraints from magmas in the eastern Betics and Rif indicate mantle melting depths between 40 and 60 km, typical of melting depths beneath mid‐oceanic ridges where little to no lithosphere exists. Together, the RF and thermobarometric data suggest ongoing and recent slab detachment resulting from delamination of the continental lithosphere.